2014
DOI: 10.1007/s10151-014-1201-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a new synbiotic supplement on symptoms, stool consistency, intestinal transit time and gut microbiota in patients with severe functional constipation: a pilot randomized double-blind, controlled trial

Abstract: An 8-week treatment with Psyllogel Megafermenti(®) improved the main clinical parameters of functional constipation in patients extremely homogeneous for disorder severity and underlying pathophysiology ( Eudract.ema.europa.eu , No. 2008-000913-30).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…The benefits of pro, pre or synbiotic supplementation are known as beneficial to gut functionality. Studies similar to ours, in any way, have shown that probiotic intake (which are related to synbiotic) is capable of improving constipation in general population; the benefits pointed by the studies included increasing in the colonic transit (30) ; improvement in evacuation frequency (31) ; improvement in stool consistency (32) , among others. The benefits of these substances seem to be more pronounced when planned to specific groups, such as the ones diagnosed as functional constipation (33) .…”
Section: Discussionsupporting
confidence: 65%
“…The benefits of pro, pre or synbiotic supplementation are known as beneficial to gut functionality. Studies similar to ours, in any way, have shown that probiotic intake (which are related to synbiotic) is capable of improving constipation in general population; the benefits pointed by the studies included increasing in the colonic transit (30) ; improvement in evacuation frequency (31) ; improvement in stool consistency (32) , among others. The benefits of these substances seem to be more pronounced when planned to specific groups, such as the ones diagnosed as functional constipation (33) .…”
Section: Discussionsupporting
confidence: 65%
“…Of the remaining 27 which were analyzed in detail, nine studies evaluated prebiotics or synbiotics for other diseases, two studies did not have a control group, two studies had no extractable data, in one study, synbiotics were given with laxative. As a result, we included five RCTs [17,[22][23][24][25] involving 199 patients who used prebiotics and eight RCTs [16,[26][27][28][29][30][31][32] involving 825 patients who used synbiotics. A flow diagram of studies identified in the search is shown in Figure 1.…”
Section: Eligible Rctsmentioning
confidence: 99%
“…Of the 13 included trials, nine used a parallel-group design [16,17,23,24,[26][27][28][29][30] and four used a crossover design [22,25,31,32] . These studies were performed in Argentina [31] , Brazil [17,27,29] , Finland [22,25] , Italy [16] , Iran [26] , Japan [30,32] , Malaysia [28] , Spain [23] , and the United Kingdom [24] . Sample sizes analyzed in the studies ranged from 14 to 266 participants, and follow-up ranged from 7 to 56 days.…”
Section: Eligible Rctsmentioning
confidence: 99%
See 1 more Smart Citation
“…Undernutrition, a condition widely present among hospitalised patients, further impairs the immunologic/inflammatory response, thus increasing the risk of infections (2) . Symbiotics, 'a mixture of probiotics and prebiotics that beneficially affects the host by improving the survival and implantation of live microbial dietary supplements in the gastrointestinal tract, by selectively stimulating the growth and/ or by activating the metabolism of one or a limited number of health-promoting bacteria, and thus improving host welfare' (3) , have been reported to affect intestinal function and permeability (4) . The mechanisms of action can be related to the modulation of the intestinal barrier function, the production of cytokines and immunoglobulins with anti-inflammatory properties, and the capacity to compete against pathogenic bacteria and inhibit their adherence, thus reducing gut permeability and decreasing BT.…”
mentioning
confidence: 99%